Marketing Creativity as a Microfoundation of Marketing Capability in SMEs - Rois, Tatang; Adhi Wibowo; Andhi Johan (Universitas Kuningan, 2025)
This study examines the role of marketing creativity as microfoundations of marketing capabilities and its influence on marketing performance in Small and Medium Enterprises (SMEs). Previous literature shows that marketing capabilities are key to successful marketing performance, but the micro-mechanisms that shape these capabilities remain unclear. Based on the microfoundations perspective, marketing creativity acts as a micro-mechanism in building marketing capabilities, which ultimately improves marketing performance. This study uses a quantitative approach with an explanatory survey design and Structural Equation Modelling–Partial Least Squares (SEM-PLS) analysis. The results show that marketing creativity has a positive effect on marketing capabilities, and marketing capabilities have a positive effect on marketing performance. These findings contribute theoretically to the literature on marketing capabilities through the micro-mechanism perspective and have practical implications for SMEs in strengthening their competitiveness through marketing creativity and strong marketing capabilities. Keywords: marketing creativity, marketing capability, marketing performance, SMEs, microfoundations